(3TQM GdCNHGQ aj aVGFd GdCFeI GdCWgGQs - (3GdbGVj GdfYeGf Hf Mjhf , CHh Mfjag GdfYeGf Hf eMeO Hf efUhQ Hf CMeO Hf Mjhf GdeUQj,J (B363 (3g` s
(3ChdgG (B:s
(3GdLRA GdChd efg ai aVGFd CejQ GdeDefjf GdMeO ddg GdChd HdG MO BKQJ ef GdCNHGQ hLeYJ ef GdBKGQ ai aVd GdCFeI GdCHQGQ s
(3BNQgG (B:s
(3hGddg YR hLd jbhd hgh CUOb GdbGFdjf (B( (3aGSCdhG Cgd GdPcQ Ef cfJe dGJYdehf (B) (3Je GdLRA GdKGef ef cJGH TQM GdCNHGQ ai aVGFd GdCFeI GdGWgGQ GdCHQGQ GdCNjGQ jJdhg GdLRA GdJGSY efg HYhf Gddg s
(3HgG fXGe GdJYbjHIs
(3ai GdeYgO fSNI CNQi HQbe (B711 (3JGQjNs
(3GdQHY GdChd hGdKGfi jJVef GdCLRGA ef GdChd Edi GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B106s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B201 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B324 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B136 s
Keywords: (3GdJGQjNs